THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE QUALITY OF EDUCATIONAL PROGRAMS - KHRUPOVYCH, Svitlana; BORYSOVA, Tetiana; KHRUPOVYCH, yuriy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents the author’s perspective on the impact of artificial intelligence on the quality of educational programs. It notes that the researchers were involved in the creation, implementation, and accreditation of such programs. Both the positive and negative consequences of AI for higher education students are identified. The influence of distance learning on students’ knowledge is also assessed. It is documented that changes in the quality of educational programs began at the end of 2022, when participants in the educational process started using Chat GPT. Based on a review of literary sources and personal observations, it has been identified that generative AI can pose challenges to students in acquiring high-quality knowledge. It is proven that the content of academic disciplines and teaching methodologies require revision and updating due to the influence of AI tools. The key challenges in implementing educational programs are outlined. Among them, the main issues include the percentage of elective components and the use of an individualized approach to students in specialized programs. It is established that to ensure quality learning outcomes, AI technologies should be used to acquire factual knowledge. However, in analytical and research work, students should independently draw conclusions and make proposals. As an example, the results of changes in the curriculum for students in the "Marketing" educational program are presented. Higher education students practice how AI facilitates client relationships and allows for the management of interactions between market participants. Emphasis is placed on the potential concerns of students regarding data security and confidentiality. Attention is drawn to the need to revise the "Teaching and Assessment" section of educational programs. It is noted that when evaluating written assignments, it is essential to consider that the Chat GPT chatbot can quickly complete such tasks. Therefore, a shift in assessment methods in higher education is proposed. A system is suggested where students solve more problems in classrooms, requiring them to accumulate knowledge on specific issues.